The power of positive touch: a qualitative and quantitative study of the impact of daily peer massage in five primary schools in Nottinghamshire, England. (2nd October 2018) - Pringle, Alan; McLennan, Jane; Bateman, Pip; Smith, Mike
ABSTRACT: The purpose of this study was to evaluate the benefits of peer massage for primary school children. A short peer massage routine was taught to pupils in five schools and evaluation was carried out to assess the impact that the process had on the pupils' well-being, empathy, social skills and confidence. The impact of the intervention was measured by analysis of self-reported data from the pupils using a specifically designed evaluation tool. These results were compared to results from control groups in the same schools who were not involved in the daily massage. Class teachers evaluated the impact that the process had on the pupils and commented on the relationship between massage and subsequent behaviour and performance at school. In the area of well-being, the results for the massage group showed that they felt calmer and less worried than the control group. In the area of confidence, the children receiving massage clearly felt more confident in talking to children they did not know. These changes were supported by the teachers' evaluations and comments; improved concentration in class was also noted. A less conclusive picture emerged in the social skills and empathy sections. This may suggest that the biggest impact of the programme was the way in which the process was internalised by the children. Feeling calmer, less worried and having more confidence can have a huge impact on the ability to develop lifelong coping strategies for managing the stresses and difficulties that life can bring and maintaining good mental health.